Budaya Sibaliparriq: Motivasi Berwirausaha di Kalangan Suku Mandar - Firman, Ahmad; Latief, Fitriani; Hidayat, Andi Ircham; Nooviar, Muh. Syilfa; Adnan, Arfandi; Naim, Mardjani Aliyah Abdul; TM, Ridwan (Jurnal Manajemen STIE Muhammadiyah Palopo, 2024)
Abstract The Mandar people have a cultural pattern of interaction called Sibaliparriq. Sibaliparriq (mutual help between husband and wife), both in domestic life and in wider society. This research aims to understand the role of Sibaliparriq culture in motivating interest in entrepreneurship among the Mandar community. This is important because it can provide insight into how local culture can be used as a means to maintain cultural identity and stimulate entrepreneurial activity that supports local economic growth. This research uses an exploratory qualitative research design. A qualitative approach will make it possible to gain an in-depth understanding of the implementation of Sibaliparriq cultural values in entrepreneurial motivation among the Mandar community. The population of this research are members of the Mandar community who are entrepreneurs or who have entrepreneurial experience. Participants will be selected using a purposive sampling method. The data collection techniques used were interviews, field observations and document analysis. Then the collected data will be analyzed using a descriptive analysis approach. The research results found that Sibaliparriq culture in Mandar society emphasizes the values of kinship, solidarity and mutual help between husband and wife as the core of social interaction. Apart from being a tradition, this culture is one of the main factors that motivates individuals to support each other in everyday life through entrepreneurship. Even though it faces the challenges of globalization, Sibaliparriq remains relevant as a social glue that strengthens relationships and unity in achieving shared prosperity.Keywords: Culture, Motivation, Entrepreneurship, SiballiparriqAbstrak Masyarakat Mandar memiliki suatu budaya pola interaksi yang disebut Sibaliparriq. Sibaliparriq (tolong-menolong antara suami istri), baik dalam kehidupan rumah tangga maupun dimasyarakat luas. Penelitian ini bertujuan untuk memahami peran budaya Sibaliparriq dalam memotivasi minat berwirausaha di kalangan masyarakat Mandar. Ini penting karena dapat memberikan wawasan tentang bagaimana budaya lokal dapat digunakan sebagai sarana untuk mempertahankan identitas budaya dan merangsang aktivitas berwirausaha yang mendukung pertumbuhan ekonomi lokal. Penelitian ini menggunakan desain penelitian kualitatif eksploratif. Pendekatan kualitatif akan memungkinkan untuk mendapatkan pemahaman yang mendalam tentang implementasi nilai-nilai budaya Sibaliparriq dalam motivasi berwirausaha di kalangan masyarakat Mandar. Populasi penelitian ini adalah anggota masyarakat Mandar yang berwirausaha atau yang memiliki pengalaman berwirausaha. Partisipan akan dipilih dengan metode purposive sampling. Teknik pengumpulan data yang digunakan adalah wawancara, observasi lapangan dan analisis dokumen. Kemudian Data yang dikumpulkan tersebut akan dianalisis menggunakan pendekatan analisis deskriptif. Hasil penelitian menemukan bahwa Budaya Sibaliparriq dimasyarakat Mandar menekankan nilai kekerabatan, solidaritas, dan tolong-menolong antara suami istri sebagai inti interaksi sosial. Selain menjadi tradisi, budaya ini menjadi salah satu faktor utama yang memotivasi individu untuk saling mendukung dalam kehidupan sehari-hari dengan berwirausaha. Meskipun dihadapi tantangan globalisasi, Sibaliparriq tetap relevan sebagai perekat sosial yang memperkuat hubungan dan kesatuan dalam mencapai kesejahteraan bersama.Kata Kunci: Budaya, Motivasi, Siballiparriq, Wirausaha